The History of Socio-Economic Processes in Uzbekistan on the Example of Individual Regions (In the 20s of the Xx Century) - Maxamatjonovich, Normatov Otabek (European Journal of Life Safety and Stability (2660-9630), 2022)
This article describes the social and economic life in Uzbekistan on the eve of the zoning policy implemented in Central Asia. Based on the data and historical materials presented in various archival sources, the general state of agriculture, trade relations, industry, agriculture, crafts, animal husbandry in Tashkent, Samarkand and Kokand districts on the eve of the zoning policy is analyzed.